COMPARISON OF INDONESIAN POPULATION GROWTH BY PROVINCE 1995-2015 BASED ON SUPAS DATA - Desi Lestari (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2019)
The Inter-Census Population Survey (SUPAS) was conducted for the benefit of national data. The analysis of this research uses a qualitative approach with literature study. Research data is obtained from the Central Bureau of Statistics (BPS) and other references such as books and journals. The data obtained relates to the problem of comparing Indonesia's population growth by province from 1995 to 2015 based on SUPAS data.